Identifying methodology to investigate cost data input in life cycle cost analysis of a building - Ayob, Mohd Fairullazi; Abdul Rashid, Khairuddin (THOMSON REUTERS, 2014)
Purpose –Life Cycle Cost (LCC) estimation process can be divided into three main phases: data inputs, conversion and outputs. The objective of this paper is to identify the most appropriate methodology to investigate the quality of data used as inputs in LCC estimation for building works in the Malaysian construction industry. The focus of quality data here is cost data inputs of building LCC. This paper reports part of a three-year research programme to enhance quality of LCC outputs through the enhancement of quality data input requirements.